Cognitive tasks elicit mental fatigue and impair subsequent physical task endurance: Effects of task duration and type. (21st June 2022) - Dallaway, Neil; Lucas, Samuel J. E.; Ring, Christopher
Abstract: Although mentally fatiguing cognitive tasks can impair subsequent physical endurance, the importance of cognitive task duration and the role of response inhibition remain unclear. This study compared the effects of a serial incongruent Stroop color‐classification task (i.e., with response inhibition) and N‐back memory updating task (i.e., without response inhibition) on mental fatigue and subsequent rhythmic handgrip exercise. Participants ( N  = 90) were randomly assigned to one of three cognitive task groups (Stroop, 2‐back, control) and completed four 10‐min blocks of one cognitive task followed by a 5‐min physical endurance task (self‐paced rhythmic handgrip exercise). Heart rate, heart rate variability, electromyographic forearm activity, and force were recorded throughout along with self‐reported measures of fatigue, exertion, and motivation. From the start, the Stroop and 2‐back tasks elicited higher heart rate and lower heart rate variability as well as greater fatigue, effort, and interest/enjoyment than the control task. From the second block onwards, the Stroop and 2‐back groups produced less force than the control group. There were no group differences in forearm muscle activity. In sum, mental fatigue was induced after performing a cognitive task for 10 mins, whereas muscular endurance was impaired after performing a cognitive task for 20 mins. That these effects were observed for both types of cognitive task indicates that response inhibition is not a necessary condition. The cognitive task duration required to induce mental fatigue and impair rhythmic handgrip endurance performance lay between the durations reported previously for isometric (a few minutes) and whole‐body (half an hour) endurance exercise. Abstract : Mental fatigue can impair physical performance. We determined the importance of cognitive task type and duration on fatigue and performance. Both memory updating (2‐back) and response inhibition (Stroop) tasks elicited comparable fatigue after 10 min. Subsequent physical performance was impaired after 20–40 min. The fatigue‐performance relationship depended on task duration but not type of executive function.